Chemical structural characteristics of high inertinite coal. (15th February 2021) - Lin, Hualin; Wang, Yehan; Gao, Shansong; Xue, Yuan; Yan, Chunyang; Han, Sheng
Highlights: Inertinite-rich in raw coal were further separated into two different densities via density flotation. There is a progressive difference in different components of inertinite. Quantum chemical calculation can be used to evaluate the reactivity of coal. Abstract: Inertinite content is a main factor affecting oil yield. In this study, raw coal with high inertinite content was selected to investigate the chemical structural characteristics of inertinite of different densities. Inertinite-rich (>1.30 kg/L) in raw coal was further separated into low (LDI, 1.30–1.38 kg/L)- and high (HDI, >1.38 kg/L)-density samples via density flotation. Structural models of raw coal, LDI, and HDI were built on the basis of the analytical results obtained from solid-state 13 C nuclear magnetic resonance, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The characterization data and molecular structural models showed no significant difference in the aromaticity of raw coal, LDI, and HDI, and the types and quantities of structural units in all samples were nearly identical. Bond length and bond order data obtained by using quantum chemical calculation were simultaneously combined with the molecular structural models, and raw coal, LDI, and HDI demonstrated progressive differences in number of active breaks of chemical bonds and fragment structures after bond breakage.